PROFILE POWER: THE LINKEDIN TACTICS AND APPROACHES OF FINAL YEAR STUDENTS - Beisembay, Almira (Nazarbayev University School of Sciences and Humanities, 2025)
This study explores how final-year students at Nazarbayev University see and use LinkedIn as they prepare to enter the job market. It examines their motivations for joining the platform, how they curate their profiles, and the benefits they gain from active use. The research uses a qualitative, phenomenological approach to understand students’ personal experiences and perceptions of LinkedIn. Six final-year students from four different majors, all with active LinkedIn profiles, shared how they present themselves professionally and manage their online image. Findings show that LinkedIn is more than just a job-search tool, as it plays a key role in shaping students’ professional identities and career paths. The study also reveals gender differences in how students perceive the platform and highlights its impact on mental wellbeing.
Keywords: LinkedIn; Social Media; Career Development; type of access: embargo